Study of the Fuzzy Optimal Solution of Fully Fuzzy Linear Programming Problems (International Journal of Scientific Research in Science and Technology, 2024)
In this paper, a new method is proposed to find the fuzzy optimal solution of fully fuzzy linear programming problems with triangular fuzzy numbers. The proposed method is very easy to understand and to apply for fully fuzzy linear programming problems occurring in real life situations as compared to the existing methods.